Inflammatory Signaling and Aryl Hydrocarbon Receptor Mediate Synergistic Induction of Interleukin 6 in MCF-7 Cells - Hollingshead, Brett D. (2008)
The pleiotropic cytokine interleukin 6 (IL-6) is involved in immune cell homeostasis. Additionally, IL-6 expression and signaling in tumor cells have been shown to elicit both protumor and antitumor properties. There is a plethora of mechanistic knowledge regarding how IL-6 signal transduction translates to biological responses. However, there is little understanding as to what factors control IL-6 expression within a tumor cell environment. The studies presented herein show that, in MCF-7 breast and ECC-1 endocervical cancer cells, the stimulation of aryl hydrocarbon receptor (AHR) activity, in combination with IL-1B or phorbol 12-myristate 13-acetate (PMA) treatment, results in a marked synergistic induction of IL-6 levels over what is seen without AHR activation. Chromatin immunoprecipitation experiments suggest that the regulation of IL-6 mRNA expression occurs at the chromatin level, as AHR presence on the IL-6 promoter was observed in response to treatment with AHR ligand. Synergistic induction of IL-6 expression was sustained for 72 hours, with accumulation of IL-6 protein reaching levels 4.8-fold above IL-1B treatment alone. In addition, transcriptional regulation of the prototypic AHR responsive gene Cyp1a1 was negatively regulated by PMA and IL-1B treatment. Silencing of RELA expression alleviated IL-1B–mediated repression of AHR transcriptional activity, whereas PMA-mediated repression was maintained. Additionally, small interfering RNA studies reveal that AHR and RELA are necessary for synergistic induction of IL-6. The findings presented here reveal the AHR as a potential therapeutic target for selective modulation of IL-6 expression in some tumor cell types. The data also suggest a possible previously unrecognized mechanism of AHR-mediated tumor promotion.